Physiological and biochemical responses of plants in saline environment - Torabi, Masoud; Abd Halim, Mohd Ridzwan; Mokhtarzadeh, Aliakbar; Miri, Yasamin (Lambert Academic Publishing, 2013)
Salinity affects plant growth and development in various ways through its impact on photosynthesis, water relations and nutrient absorption. Additionally, the biochemical composition of plants is also affected by salinity through changes in the concentration and type of proteins, amino acids, sugars and other carbohydrates. This chapter elucidates with examples the changes that occur in the plant‟s physiological functions and biochemical composition as a result of increased salinity of the plant‟s environment. It is highlighted that the fundamental mechanism of salinity‟s effects on plant function is the increase in the osmotic pressure of the plant‟s environment that inhibits the absorption of water and nutrients. Invariably, salinity inhibits photosynthesis through its effects on stomatal conductance, water and nutrient uptake and decrease in the chlorophyll concentration. Subsequently, higher levels of salinity create an excessive accumulation of salts in plant tissues that causes toxicity. Prolonged salinity will thus reduce plant growth and yield and with increasing severity of salinity, toxic levels of salts that build up in plant tissues will further aggravate the stress. Plants exhibit several mechanisms that can alleviate the deleterious effects of salinity including compartmentalization of ions, synthesis of compatible solutes, induction of plant hormones and alteration of membrane structure.